Concomitant Enhancement of HIV-1 Replication Potential and Neutralization-Resistance in Concert With Three Adaptive Mutations in Env V1/C2/C4 Domains - Doi, Naoya; Yokoyama, Masaru; Koma, Takaaki; Kotani, Osamu; Sato, Hironori; Adachi, Akio; Nomaguchi, Masako (Frontiers in microbiology, 2019)
HIV-1 Env protein functions in the entry process and is the target of neutralizing antibodies. Its intrinsically high mutation rate is certainly one of driving forces for persistence/survival in hosts. For optimal replication in various environments, HIV-1 Env must continue to adapt and evolve through balancing sometimes incompatible function, replication fitness, and neutralization sensitivity. We have previously reported that adapted viruses emerge in repeated and prolonged cultures of cells originally infected with a macaque-tropic HIV-1 derivative. We have also shown that the adapted viral clones exhibit enhanced growth potentials both in macaque PBMCs and individuals, and that three single-amino acid mutations are present in their Env V1/C2/C4 domains. In this study, we investigated how lab-adapted and highly neutralization-sensitive HIV-1 adapts its Env to macaque cells with strongly replication-restrictive nature for HIV-1. While a single and two mutations gave a significantly enhanced replication phenotype in a macaque cell line and also in human cell lines that stably express either human CD4 or macaque CD4, the virus simultaneously carrying the three adaptive mutations always grew best. Entry kinetics of parental and triple mutant viruses were similar, whereas the mutant was significantly more readily inhibited for its infectivity by soluble CD4 than parental virus. Furthermore, molecular dynamics simulations of the Env ectodomain (gp120 and gp41 ectodomain) bound with CD4 suggest that the three mutations increase binding affinity of Env for CD4 in solution. Thus, it is quite likely that the affinity for CD4 of the mutant Env is enhanced relative to the parental Env. Neutralization sensitivity of the triple mutant to CD4 binding site antibodies was not significantly different from that of parental virus, whereas the mutant exhibited a considerably higher resistance against neutralization by a CD4-induced epitope antibody and Env trimer-targeting V1/V2 antibodies. These results suggest that the three adaptive mutations cooperatively promote viral growth via increased CD4 affinity, and also that they enhance viral resistance to several neutralization antibodies by changing the Env-trimer conformation. In total, we have verified here an HIV-1 adaptation pathway in host cells and individuals involving Env derived from a lab-adapted and highly neutralization-sensitive clone.